Executive functions as moderators of the neuroticism-burnout relationship - Bailey, Tom James (2017)
Whilst the positive relationship between neuroticism and burnout is well-established within the extant literature, it is also acknowledged that neurotic individuals may differ in the extent to which they experience such detriments in well-being. In concordance with dual-processing theories of behaviour, it was suggested in this thesis that executive functions may enable one to enact in a ‘goal-orientated’ manner, and thus overcome one’s instinctive neurotic tendencies towards burnout.